Diabetes self-care and its associated factors among elderly diabetes in primary care. Issue 6 (December 2017) - Ishak, Nor H.; Mohd Yusoff, Siti S.; Rahman, Razlina A.; Kadir, Azidah A.
الملخص: أهداف البحث: داء السكري في المقام الأول هو داء يمكن التحكم فيه ذاتيا. ويقدم متخصصو الرعاية الصحية التعليم، والعلاج، والمساندة، ولكن المرضى هم المسئولين عن الإدارة اليومية لحياتهم. يمكن أن يكون لزيادة فعالية-الدعم الذاتي تأثير كبير على الرعاية الصحية، خاصة لدى كبار السن. وتهدف هذه الدراسة إلى وصف الرعاية الذاتية لداء السكري بين مرضى السكري المسنين، وتحديد العوامل المرتبطة به. طرق البحث: ضمت هذه الدراسة المقطعية ١٤٣ من مرضى السكري المسنين، في العيادات الخارجية للمستشفى الجامعي في سينز ماليزيا. بحيث قيمت أنشطة الرعاية الذاتية متضمنة السيطرة الغذائية، والنشاط البدني، والرصد الذاتي للجلوكوز بالدم، والالتزام بالدواء، وسلوك الالتزام المتعلق بالمواقف، التي تم الحصول عليها باستخدام استبانة مالاي للرعاية الذاتية لمرضى السكري المسنين. النتائج: كان متوسط أعمار المشاركين ( ± الإنحراف المعياري) ٦٧.٩(±٥.٤) عاما. وكان معظمهم من مالاي، ومتوسط الهيموجلوبين السكري ٨.٤ (±١.٩). وكان متوسط درجة الرعاية الذاتية لداء السكري ٢٦.٥ (±٨.٠). والعوامل التي لها تأثير موجب على الرعاية الذاتية لداء السكري تشمل: كون المريض ليس من مالاي، ولديه أسرة مقدمة للرعاية، ودعم أسري أكبر، وامتلاك معرفة مقبولة بداء السكري، والمعرفة الجيدة. ووجود الاعتلال العصبي يؤثر سلبا على الرعاية الذاتية، بينما للاعتلال الكلوي تأثير إيجابي. الاستنتاجات: لدى كبار السن المصابون بداء السكري النوع ٢، درجة معتدلة من ممارسة الرعاية الذاتية لداء السكري بناء على استبانة مالاي للرعاية الذاتية لمرضى السكري المسنين. وتشمل محددات الممارسة الجيدة للرعاية الذاتية لداء السكري العِرق، والدعم الاجتماعي، ووجود مقدمي الرعاية أثناء فترات المرض، والمعرفة بداء السكري، ومضاعفات الأوعية الدموية لداء السكري. Abstract: Objectives: Diabetes is a primarily self-manageable condition. Healthcare professionals usually offer education, treatment, and support, but patients themselves are responsible for the daily management of their condition. Increasing the effectiveness of self-management support may have a considerable impact on health care, especially for elderly people. The aim of this study was to describe diabetes self-care among elderly diabetics and to determine its associated factors. Methods: This report describes a cross-sectional study involving 143 elderly diabetes patients in the outpatient department of the Hospital Universiti Sains Malaysia (HUSM). Self-care activities assessed in this study included dietary control, physical activity, self-monitoring of blood glucose, medication adherence, and situational related adherence behaviour, all of which were obtained using the validated Malay Elderly Diabetes Self-Care Questionnaire (MEDSCaQ). Results: The mean (±SD) age of the subjects was 67.9 (±5.4) years old. A majority was Malay, with a mean HbA1c of 8.4 (±1.9). The mean diabetes self-care score was 26.5 (±8.0). Factors with a positive impact on diabetes self-care included being non-Malay (β = 5.275, p = 0.002), having family as care givers (β = 8.995, p = 0.004), having a higher level of family support (β = 0.159, p = 0.042), and possessing acceptable (β = 4.375, p = 0.001) or good knowledge of diabetes (β = 5.893, p = 0.004). The presence of neuropathy negatively impacted self-care, while diabetes nephropathy had a positive impact on self care (β = −4.053, p = 0.003). Conclusions: Elderly individuals with type 2 diabetes in HUSM have a moderate score of diabetes self-care practice based on the MEDSCaQ. Determinants for good diabetes self-care include race, social support, having care-takers during periods of illness, diabetes knowledge, and diabetic microvascular complications.